The Case of Hagia Sophia's Opening to Worship As an Example of Political “Anamnesis” - Deniz Ülke Arıbogan (Journal of Economy Culture and Society)
Hagia Sophia has a history of 1500 years. It has been used as a church for nearly 1000 years and has become a crucial symbol of the power of the Byzantine Empire as well as being a center of worshipping for Christians. The symbolic power of Hagia Sophia, which was used as a mosque for 482 years and was conquered by Ottomans, is important. The conquest of Istanbul has been designated by Prophet Muhammed as a 'heralded victory' or 'chosen destination' and therefore, it has a very different meaning for the Islamic world. It was converted into a museum on November 24, 1934. This decision can be interpreted as neutralizing the space in terms of religion or as an effort to compromise. The issue of whether Hagia Sophia is to be reopened as a mosque or not is discussed from time to time in nationalist-conservative discourse. It has been a monumental place that has important symbolic meanings for different religions and empires throughout history and has caused victories, sadness, joys, losses and collective traumas. These old-world traumas are instrumentalized again in the new world. In this paper, the subject will be discussed in the context of political anamnesis.